THE INFLUENCE OF SOCIOECONOMIC STATUS ON THE MODES CHOICE OF TRANSPORTATION IN MANADO CITY - Sompie, Tampanatu Parengkuan Fransiscus (Journal of Applied Engineering Science, 2022)
Good infrastructure and transportation facilities move people and goods take place safely and economically in terms of time and cost. The trips made by people on weekdays or weekends affect environmental conditions in the area. The purpose of this paper is to find out the influence of socioeconomic status on modes choice of transportation both on weekdays and weekends. The study location is in Manado Municipality. There are 3 (three) modes of transportation reviewed, i.e. private cars, motorcycles, and public transportation. Indicators of socioeconomics status of transportation users are age, education, occupation, income, number of family members, and vehicle ownership. Data regarding the modes of transportation and socioeconomic status of travelers were obtained through questionnaire surveys. SEM-AMOS was used to measure the validity and reliability of the data. The probability of the mode choice on weekdays and weekends was analyzed using multinomial logistic regression analysis. The results showed that the socioeconomic status of the traveler has an influence on the mode choice of transportation by 49.2% on weekends and 49.5% on weekdays. Furthermore, the probability of transportation mode choice on weekends is the car by 88.4%, and on weekdays is motorcycles by 71.6%.